Competitive Advantage Analysis of Scarf Brands: A Comparative Study of Ash Scarf, Brand Botton Scarf, and Umama - Zenitha Kurnia Putri; Sudarmiatin Sudarmiatin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research examines the competitive advantages of scarf brands in Indonesia by comparing three cases: Ash Scarf, Brand Botton Scarf, and Umama. The study analyzes how each brand employs differentiation and digitalization strategies to achieve a competitive edge in the market. By applying Porter's generic strategies framework and the resource-based view, this research identifies the unique value propositions, target market focus, and digital marketing effectiveness of each brand. The findings reveal distinct approaches to competitive advantage, highlighting the importance of brand positioning, product innovation, and customer engagement in the online and offline landscape.